Pie in the sky. Series 2 [videorecording (DVD)] - Skinns, Chrissy; Wimbury, David; Payne, Andrew; Milne, John; Maher, Richard; Mickery, Lizzie; Hill, Jim, 1951-; Hutchings, Martin; Hiller, Danny; Clark, Lawrence Gordon; Griffiths, Richard, 1947-2013; Steed, Maggie; et al. (Acorn Media, 2010)
Semi-retired policeman Henry Crabbe would rather be cooking than catching criminals. Unluckily for him, he happens to be good at both. His boss, Assistant Chief Constable Fisher doesn't want to lose him, and his accountant wife, Margaret, worries his new career as a restaurateur won't be financially viable. While indulging his culinary passions, Crabbe remains on call for those particularly tricky case that Fisher sends his way.